Dynamic Shared-Taxi Dispatch Algorithm with Hybrid-Simulated Annealing - Jung, Jaeyoung; Jayakrishnan, R.; Park, Ji Young (Computer-aided civil and infrastructure engineering, 2016)
Taxi is certainly the most popular type of on‐demand transportation service in urban areas because taxi‐dispatching systems offer more and better services in terms of shorter wait times and passenger travel convenience. However, a shortage of taxicabs has always been critical in many urban contexts especially during peak hours, and taxi has great potential to maximize its efficiency by employing the shared‐ride concept. There are recent successes in dynamic ride‐sharing projects that are expected to bring substantial benefits arising from energy consumption and operation efficiency and thus, it is essential to develop advanced shared‐taxi‐dispatch algorithms and investigate the collective benefits of dynamic ride‐sharing by maximizing occupancy and minimizing travel times in real‐time. This article investigates how taxi services can be improved by proposing shared‐taxi algorithms and what type of objective functions and constraints could be employed to prevent excessive passenger detours. Hybrid‐simulated annealing (HSA) is applied to dynamically assign passenger requests efficiently. A series of simulations are conducted with two different taxi operation strategies. The simulation results reveal that allowing ride‐sharing for taxicabs increases productivity over the various demand levels and HSA can be considered as a suitable solution to maximize the system efficiency of dynamic ride‐sharing.